2020
DOI: 10.1007/s00425-020-03421-2
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose phosphate synthase (SPS), sucrose synthase (SUS) and their products in the leaves of Miscanthus × giganteus and Zea mays at low temperature

Abstract: Main conclusion The changes in the expression of key sugar metabolism enzymes (SPS and SUS), sucrose content and arrangement of chloroplast starch may play a significant role in the cold response in M. giganteus and maize plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 61 publications
4
33
0
Order By: Relevance
“…It is possible that stress due to the supply of Cu 2+ and Ag + ions in the regeneration medium affected the status of cellulose primarily in a relatively more amorphic phase. In Miscanthus giganteum, a slight shift in the cellulose peak in this region of frequency has been observed as a result of mild chilling stress [63], which was associated with the formation of a more compact cellulose structure. The band at 700 cm −1 may be assigned not only to cellulose but also to the C-S stretching vibrations, which may be attributed to thiol or thioester functional groups.…”
Section: Discussionmentioning
confidence: 92%
“…It is possible that stress due to the supply of Cu 2+ and Ag + ions in the regeneration medium affected the status of cellulose primarily in a relatively more amorphic phase. In Miscanthus giganteum, a slight shift in the cellulose peak in this region of frequency has been observed as a result of mild chilling stress [63], which was associated with the formation of a more compact cellulose structure. The band at 700 cm −1 may be assigned not only to cellulose but also to the C-S stretching vibrations, which may be attributed to thiol or thioester functional groups.…”
Section: Discussionmentioning
confidence: 92%
“…There is still evidence that they play an important role in stress resistance. For example, Glyma.09g073600 and Glyma.18g108100 regulate sucrose-related enzymes to increase resistance to low temperature stress [42]; Glyma.04g119700 regulates maltooligosyltrehalose under salt stress [43]; Glyma.12g054200 is considered to be a factor potentially involved in regulating the salt adaptation of α -galactosidase production [44]. In addition, Baud et al [45] and Santaniello et al [46] found that the Arabidopsis thaliana At3G43190 gene homologous to Glyma.09G073600, plays an important role in the regulation of sucrose synthase activity in plant sugar metabolism, whereas Chary et al [47] found that the At1G68020 homolog of Glyma.04G119700 affects Arabidopsis cellular morphology and plant structure via the activity of trehalose -6-phosphate synthase/phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose phosphate synthase (SPS) catalyzes the conversion of fructose-6-phosphate and uridine diphosphate-glucose into sucrose-6phosphate. The activity and localization of these enzymes can be controlled by reversibility phosphorylation process controlled by calcium-dependent kinases (Bilska-Kos et al, 2020). In turn, sucrose-phosphate phosphatase (SPP) catalyzes the final step of the sucrose biosynthesis pathway.…”
Section: Reconstruction and Comparative Analysis Of Sucrose Metabolism Pathwaymentioning
confidence: 99%